SOBRE LA FORTALEZA DE MULA. APORTE DOCUMENTAL - Nicolás Martínez, Mª del Mar (Imafronte, 1999)
This paper has discovered a record of the construction of the fortress at Mula (Murcia), written by its architect, the morisco (a moslem convert to christianity). Luis Fajardo, The document provides valuable information about the state of the works. diferent expenses, the search Jor materials, etc. It also raises the intriguiny question of the possible existence of an older christian castle, before Fajardo.